Inspirasi Teologis Komunitas Kristiani dan Interpretasinya oleh Gereja Mahasiswa (GEMA) Bandung - Pratama, Dominius Kristian; Tedjoworo, Hadrianus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2023)
A community is a collection of individuals who are related to one another and are aware of their membership. Relationships among the community members are based on shared beliefs, goals, activities, or interests. This article traces the development of ideas about Christian community in the Scriptures, in the views of the Church fathers, theologians, and in the Church documents. Inspiration from the Scriptures is used to find the Christian vision of a community that can shape the evangelisation. The views of the Church fathers and of the later theologians are selected to provide an overview of the development of ideas about Christian communities that are more connected with the actual life of the faithful, especially the young generation. Pope Francis’ Postsynodal Apostolic Exhortation Christus Vivit (2019) is referred to in order to provide a picture of a Christian community that is more suited to the young people. Finally, the development of ideas about a Christian community will be correlated with the actual experiences of Catholic students at “Student Church” (Gema) in the Bandung Diocese, Indonesia. From this correlation, theological inspirations on the aspects of the Christian communities are further (re)interpreted from time to time by the moderator priests of Gema and are contextualised and lived in everydayness by the young Catholics studying in the city of Bandung.